Transactions on Engineering Technologies - Ao, Sio-Iong; Yang, Gi-Chul; Gelman, Len (Springer Nature Singapore : Imprint: Springer, 2016)
This volume presents selected peer-reviewed, revised and extended research articles written by prominent researchers who participated in the World Congress on Engineering 2015, held in London, UK, 1-3 July, 2015. This large international conference covered advances in engineering technologies and the physical sciences, with contributions on subjects including mechanical engineering, bioengineering, internet engineering, image engineering, wireless networks, knowledge engineering, manufacturing engineering, and industrial applications. This book offers a snapshot of the state-of-the-art, highlighting tremendous advances in engineering technologies and physical sciences and their applications, and will serve as an excellent reference for researchers and graduate students working in many different disciplines of physical sciences and engineering.